(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The textile dye Red ED3B is widely used in several textile industries and is a toxic azo dye. Owing to its complex structure, it persists in environment for longer period of time and is detrimental for environment and all living beings. Bacterial strains were isolated from the dye contaminated soil having high potential to decolorize this dye. 5 bacteria were isolated from acclimatized soil samples among which, Ochrobactrum sp. RED-3 showed decolourization of Red ED3B dye which was identified by Morphological, Biochemical and 16srRNA sequencing. The optimization of various parameters such as temperature, pH, inoculums size dye concentration, carbon and nitrogen sources was studied in order to achieve maximum dye degradation. Under optimum conditions Ochrobactrum sp. RED-3 exhibited excellent ability to degrade Red ED3B at Room temperature (97.35%), pH 9.0 (98.07%), 2% inoculum size (95.71%), dye concentration upto 800ppm (64.32%), 1% Starch (97.18%) and 1% Peptone (89.49%) as carbon and nitrogen source. Further metabolic pathway for Red ED3B degradation was predicted on the basis of GC-MS reports which confirms complete breakdown of complex dye into low molecular and non-toxic metabolites. Owing to highest efficiency for removal of Red ED3B dye, the isolate Ochrobactrum sp. RED-3 can be exploit for complete bioremediation of dye from textile effluents.